Endothelial Phosphatase VE-PTP Participates in Vasculogenic Mimicry by Preventing Autophagic Degradation of VE-Cadherin - Delgado-Bellido, Daniel; Bueno-Galera, Concepción; López-Jiménez, Laura; Garcia-Diaz, Angel; Oliver, F. Javier (Frontiers in Oncology, 2020)
Aberrant extra-vascular expression of VE-cadherin has been observed in metastasis associated with Vasculogenic Mimicry (VM); we have recently shown that in VM prone cells VE-cadherin is mainly in the form of phospho-VE-cadherin in Y658 allowing increased plasticity that potentiates VM development in malignant cells. In the current study, we present results to show that human malignant melanoma cells VM+, express the VE-cadherin phosphatase VE-PTP. VE-PTP forms a complex with VE-Cadherin and p120-catenin and the presence of this complex act as a safeguard to prevent protein degradation by autophagy. Indeed, VE-PTP silencing results in complete degradation of VE-cadherin with the features of autophagy. In summary, this study shows that VE-PTP is involved in VM formation and disruption of VE-PTP/VE-Cadherin/p120 complex results in enhanced autophagy in aggressive VM+ cells. Thus, we identify VE-PTP as a key player in VM development by regulating VE-cadherin protein degradation through autophagy .